Konsep Dasar Produktifitas Tenaga Kerja dalam Perspektif Ekonomi Islam - Nur Fadilah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
The spirit in work illustrates the aspects of good work ethics in humans, sourced from the quality of self, realized based on the value of the work ethic that is implemented in work activities. Islamic teachings strongly encourage his people to work hard, and that the teachings of Islam contain the spirit and encouragement of the growth of culture and labor productivity activities that have a balanced spiritual dimension. The work ethic in Islam is closely linked to the values contained in the Qur'an and the Sunnah about "work" -which is a source of inspiration and motivation by every Muslim to engage in work activities in various areas of life. The way they understand, live and practice the values of the Qur'an and al-Sunnah about the drive to work that form the work ethic of Islam. Islam does not neglect the role of rewards and material benefits in one's work. Islam invites managers and employers to behave well to their subordinates with the full treatment of brotherhood and also provide decent monetary compensation in the provision of wages or raising wages and welfare of the workforce, so the activity and discipline of one's work can be realized, which ultimately increases the level of work productivity the entire workforce. Based on the attitude of devotion to Allah SWT, the spirit of work and tomorrow's view with optimism, is the basis for the improvement of labor productivity, by improving education and skills supported by work ethic capable of carrying out the task of working properly, which will encourage the effort in the effort which in turn increases income, both individual, group, and national income.